Nonlinear PI control for variable pitch wind turbine. (May 2016) - Ren, Yaxing; Li, Liuying; Brindley, Joseph; Jiang, Lin
Abstract: Wind turbine uses a pitch angle controller to reduce the power captured above the rated wind speed and release the mechanical stress of the drive train. This paper investigates a nonlinear PI (N-PI) based pitch angle controller, by designing an extended-order state and perturbation observer to estimate and compensate unknown time-varying nonlinearities and disturbances. The proposed N-PI does not require the accurate model and uses only one set of PI parameters to provide a global optimal performance under wind speed changes. Simulation verification is based on a simplified two-mass wind turbine model and a detailed aero-elastic wind turbine simulator (FAST), respectively. Simulation results show that the N-PI controller can provide better dynamic performances of power regulation, load stress reduction and actuator usage, comparing with the conventional PI and gain-scheduled PI controller, and better robustness against of model uncertainties than feedback linearization control. Abstract : Highlights: Perturbation compensation based nonlinear PI type pitch-angle control for wind turbine. Nonlinear PI controller uses one set of gains for different wind speeds. Avoid tuning of PI gains and switching of gain for gain-schedule PI. Provide better power regulation and less drive-train stress and actuator usage. Simulation verification and comparison on the simplified model and the detailed FAST simulator.